Novel Variants in the MC4R and LEPR Genes among Severely Obese Children from the Iberian Population. (11th March 2014) - Albuquerque, David; Estévez, Manuela Núñez; Víbora, Pilar Beato; Giralt, Plácida Sánchez; Balsera, Aránzazu Margallo; Cortés, Pedro Gil; López, Mercedes Jiménez; Luego, Luis Miguel; Gervasini, Guillermo; Hernández, Sergio Barroso; Arroyo‐Díez, Javier; Vacas, Manuel Arrobas; et al.
Summary We screened for mutations in the MC4R and LEPR genes and investigated the genotype‐phenotype correlation in obese individuals belonging to families with evident hereditary patterns of severe and early‐onset obesity among the Iberian population. A total of 202 unrelated and severely obese patients since childhood, were enrolled in the study. Bidirectional sequencing of the MC4R gene was carried out in all patients; the LEPR gene was sequenced in 15 individuals based on additional clinical signals. Segregation analysis and/or genotype‐phenotype description was performed for subjects with the new mutations and with presumably functional variants. Ten MC4R gene mutations were identified in the heterozygous state in 10 patients. Mutations p.R147G and p.G323E are new and mutations p.R7H, p.G32E, p.H76R, p.V103I, p.S127L, p.T150I, p.I251L and p.G252S were previously described. A new dinucleotide insertion ‐77_‐76insTA in the promoter region of the LEPR gene was found in the heterozygous state in one patient. The new p.R147G and the previously published p.R7H, p.S127L, p.T150I and p.G252S MC4R mutations, cosegregate with obesity in our patients and were predicted to be deleterious. For the novel MC4R p.G323E and LEPR ‐77_‐76insTA gene mutations, the genotype‐phenotype correlation and bioinformatic analysis did not clarify whether these mutations are indeed implicated in obesity.